"A right place for everybody": Supporting aging in the right place for older people experiencing homelessness. (8th June 2022) - Weldrick, Rachel; Canham, Sarah L.; Sussman, Tamara; Walsh, Christine A.; Mahmood, Atiya; Nixon, Lara; Burns, Victoria F.
Abstract: While policies and practices that promote aging in place have risen in prominence over the last two decades, marginalised older adults have largely been overlooked. 'Aging in the right place' is a concept that recognises the importance of adequate and appropriate age‐related health and psychosocial supports in shelter/housing settings and their impact on the ability of older people to age optimally. To understand the unique shelter/housing challenges and solutions that affect aging in the right place for older people experiencing homelessness (OPEH), we conducted three World Café workshops in three Canadian cities—Montreal, Calgary, and Vancouver. In total, 89 service providers and OPEH engaged in the workshops, which involved guided, small‐table discussions with the goal of stimulating creative ideas and fostering a productive atmosphere. Findings revealed two overarching themes 1) Discrepancies, between the need and availability of housing options and community supports for OPEH, such as affordable transportation, case management, access to healthcare, and system navigation; and 2) Desires, for more peer support, participatory planning, service‐enriched housing, social programming, and policies that promote agency, independence, and choice for OPEH. These findings provide evidence to inform the development or modification of housing and supports for OPEH that promote aging in the right place.